Data from: New York State bald eagle report 2010 ... - Nye, Peter; Hewitt, Glenn; Swenson, Theresa; Kays, Roland (Movebank Data Repository, 2018)
Satellite telemetry collected between 1992 and 2010 by the New York State Department of Environmental Conservation to document the migratory pathways of raptors and owls in NY State. ...